Latest Developments of Research on the Viable Non-Culturable State of L. monocytogenes and Implications for Food Safety - Franca Rossi; Palmiro Poltronieri; Francesco Pomilio; Gabriella Centorotola (Applied Sciences)
This descriptive review summarizes the most recent findings on the induction and distribution of viable non-culturable (VBNC) Listeria monocytogenes in food production conditions and food. The aim was to obtain information on the factors that favor the transition to the VBNC state in L. monocytogenes; its resuscitation capacity; and, according to scientific articles published since 2020, how food contamination by the bacterium in a VBNC state can be prevented. The methods used for VBNC L. monocytogenes detection were also reviewed. A few studies reported the presence of VBNC L. monocytogenes in food, in which fresh produce and chicken meat were considered. Different physicochemical stresses such as exposure to disinfectants with diverse actions and essential oils, desiccation, low temperatures, absence of nutrients, high NaCl and iron concentrations, and low pH adjusted with acetic acid were reported to induce the VBNC state in L. monocytogenes. The VBNC forms of L. monocytogenes were able to regain growth and virulence. This could pose a safety risk that cannot be revealed by the standard culture-dependent methods recommended for L. monocytogenes detection. Therefore, the presence in food and food production plants of VBNC L. monocytogenes should be prevented by the appropriate use of hurdles and cleaning/disinfection procedures. The opportunity to harmonize VBNC cell detection methods for regular use in food safety evaluation also emerged.